Epidemiology of Stroke in Iran: - Ghandehari, Kavian (Galen Medical Journal, 2016)
Numerous hospital-based stroke registries have been developed in Iran during last decade. Khorasan Stroke Registry, Khorasan Posterior Circulation Stroke Registry, Khorasan Pediatric Stroke Registry and Khorasan Stroke in Young Adults Registry are among these published registries. Meanwhile, There is only one epidemiologic deigned study of stroke in Iran and Middle East. Based on this standard epidemiologic study; The crude annual incidence rate of First Ever Stroke (FES) is 139 (95% CI, 128 to 149) per 100 000; for men, 144 (95% CI, 128 to 159), and for women, 133 (95% CI, 118 to 148). The incidence rates increases significantly with each decade of life and is similar in men and women. Subtypes of FES in 81.9%Â  of patients is ischemic stroke,12.7% is intracerebral hemorrhage, and 2.4% have subarachnoid hemorrhage. The crude annual incidence rate per 100 000 inhabitants is 113 (95% CI, 104 to 123) for ischemic stroke, 18 (95% CI, 14 to 21) for intracerebral hemorrhage and 3 (95% CI, 2 to 5) for subarachnoid hemorrhage. Ischemic strokes are occurring approximately 1 decade earlier in Iran than in other countries.